Bevacizumab demonstrates activity in advanced refractory fallopian tube carcinoma. Issue 2 (1st February 2008) - Arora, N.; Tewari, D.; Cowan, C.; Saffari, B.; Monk, B. J.; Burger, R. A.
Abstract : The targeting of angiogenesis pathways in the treatment of gynecological cancers is an exciting development in cancer therapy. Bevacizumab has been shown to have activity in ovarian cancer through its inhibition of the vascular endothelial growth factor. Fallopian tube carcinoma is a rare malignancy and is often treated in a similar manner as ovarian carcinoma. We present a case of a complete response in a woman with refractory metastatic fallopian tube carcinoma treated with bevacizumab. This report demonstrates the significance of anti-angiogenesis therapy in the treatment of these tumors.